The effect of library exterior design building on increasing student's personal branding through selfie - Wicaksono, Moch Fikriansyah; Al As'hal, Ajrun ‘Azhim; Attri, Rajeev Kumar (Record and Library Journal, 2023)
Background of the study: The exterior design of the library building is an alternative in attracting visitors to come and visit. However, in reality this is not only limited as a means of promotion, it can even be a means of enhancing personal branding. This situation is currently happening to student of IPII UIN Sayyid Ali Rahmatullah Tulungagung who like to take selfies with the exterior view of the library building Purpose: This research aims to explain the effect of the exterior design of the UIN Sayyid Ali Rahmatullah library building on increasing student personal branding through selfies Method: This research uses quantitative methods with explanative approach. Data collection techniques through questionnaires, literature study, and observation. The population and sample were 50 students of IPII at UIN Sayyid Ali Rahmatullah Tulungagung who took selfies with the exterior background of the library building and used quota sampling for sampling. Findings: The results explain that there is an influence between the exterior design of the library building on student personal branding through selfies with a significance value of 0.000<0.005 and an influence value of 35.3%. Conclusion: The exterior design of the UIN Sayyid Ali Rahmatullah Tulungagung library building had a significant impact on the personal branding of IPII students in the form of an increase in the number of likes, followers, comments, viewers. Some even got Paid Promote offers and endorsements